Understanding the influence of test specimen boundary conditions on material failure resulting from artificial lightning strike. (August 2020) - Millen, S.L.J.; Murphy, A.
Highlights: Quantification of boundary conditions on material failure during lightning strike. Thermal damage found to be dependent on electrical potential boundary conditions. Delamination and damage depth found independent of mechanical boundary conditions. Abstract: This paper examines the influence of test specimen boundary conditions on material failure during an artificial lightning strike. A finite element simulation approach is employed which in contrast to an experimental investigation enables the study of material damage during the event.Specimen boundaries, representing the range of conditions found in published experimental works, are examined. Unprotected carbon fibre / epoxy composite material and Society of AutomotiveEngineers (SAE) lightning test Waveform A are studied. Damage predictions with two simulation types (coupled thermal-electric; dynamic, coupled temperature-displacement, explicit) are reported and comparisons made with experimental measurements. The results demonstrate that delamination area is sensitive to specimen boundaries, varying by over 300% for the studied conditions.Thermal damage demonstrates noteworthy interactions between the base and side surface grounding conditions, illustrating the variation of local material thermal loading with boundary condition variation. Both delamination and critical damage depth appear to be independent of mechanical boundaries, whereas the prediction of thermal damage appears highly sensitive to the selection of the specimen electrical potential boundary conditions. This paper, for the first time, establishes the effect of test specimen boundary conditions on material failure, representing a common specimen, with a single material data set and subjected to a single consistent artificial lightning component waveform.